Development of outdoor air parameters for designing air-conditioning systems according to the guarantee coefficient - Chan, Tran Ngoc; Phuong, Nguyen Thi Khanh; Quang, Tran Ngọc (Edelweiss Applied Science and Technology, 2025)
When designing the air conditioning system, it is necessary to select outdoor air calculation parameters for determining the cooling and heating loads. The pair of parameters, including enthalpy I and dry temperature t of the outdoor air, are used directly in the calculation process. The article outlines the meaning of the limit lines of the cooling/heating capacity and the airflow of an air conditioning system and presents the concept of the guarantee coefficient of the pair of parameters I and t according to the theory of probability of two events occurring simultaneously. From these, computer software was built to determine the types of guarantee coefficients Kbd and outdoor air calculation parameters for designing the air conditioning system according to the number of hours m (hours/year) that unguaranteed the indoor thermal–humidity regime. The proposed calculation method has been implemented for 30 localities in Vietnam, calculated according to twelve m values, using meteorological data over the most recent 26-30 years, which will be used to update the Vietnamese Standard for Ventilation and Air Conditioning Design (TCVN 5687:2024). The comparison of the outdoor air calculation parameters built by the guarantee coefficient method and those offered by ASHRAE for Hanoi, Vietnam, has also been carried out.